2014
DOI: 10.1158/2326-6066.cir-13-0158
|View full text |Cite
|
Sign up to set email alerts
|

CALGB 150905 (Alliance): Rituximab Broadens the Antilymphoma Response by Activating Unlicensed NK Cells

Abstract: Natural killer (NK) cells contribute to clinical responses in patients treated with rituximab, but the rules determining NK cell responsiveness to mAb therapies are poorly defined. A deeper understanding of the mechanisms responsible for antibody-dependent cellular cytotoxicity (ADCC) could yield useful biomarkers for predicting clinical responses in patients. Unlicensed NK cells, defined as NK cells lacking expression of an inhibitory KIR for self-HLA class I ligands, are hypo-responsive in steady-state, but … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
56
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 60 publications
(82 reference statements)
3
56
2
1
Order By: Relevance
“…[17][18][19] These observations were also made in lymphoma patients treated with rituximab suggesting KIR/ KIRL-dependent effects in NK-mediated tumor cell lysis. 20 Surprisingly, in the present study we did not find significant differences in ADCC and EFS between matched and mismatched inhibitory KIR/KIRL genotypes in our patient cohort (data not shown), indicating only a minor role for exclusive consideration of the 2DL3/HLA-C1 and 3DL1/HLA-Bw4 KIR/KIRL repertoire. Interestingly, analysis of patients with combined unfavorable genotypes revealed significantly decreased EFS rates in 2DS2-negative missing patients with the inhibitory 3DL1/HLA-Bw4 match, again emphasizing the important contribution of 2DS2 to the efficacy of immunotherapy with ch14.18/CHO.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…[17][18][19] These observations were also made in lymphoma patients treated with rituximab suggesting KIR/ KIRL-dependent effects in NK-mediated tumor cell lysis. 20 Surprisingly, in the present study we did not find significant differences in ADCC and EFS between matched and mismatched inhibitory KIR/KIRL genotypes in our patient cohort (data not shown), indicating only a minor role for exclusive consideration of the 2DL3/HLA-C1 and 3DL1/HLA-Bw4 KIR/KIRL repertoire. Interestingly, analysis of patients with combined unfavorable genotypes revealed significantly decreased EFS rates in 2DS2-negative missing patients with the inhibitory 3DL1/HLA-Bw4 match, again emphasizing the important contribution of 2DS2 to the efficacy of immunotherapy with ch14.18/CHO.…”
Section: Discussioncontrasting
confidence: 70%
“…[17][18][19] Similar observations were made in lymphoma patients treated with rituximab. 20 Extending on these results, interactions of activating KIR/KIRL has been recently studied in a number of malignancies. 8 Underlying the diversity of KIR genomic regions, there are patterns that are conserved within the population suggesting conservation of distinct haplotypes that can be separated into two main groups described as haplotypes A and B.…”
Section: Introductionmentioning
confidence: 98%
“…To the best of our knowledge, such a direct killing was not documented previously, likely because CD56 + NK cells are rarely detected in FL microenvironment, and MHC class I expression by FL cells typically acts as a negative control for NK cell activation. Of note, FL cell killing by NK cells generally was shown to rely on Ab-dependent cellular cytotoxicity activity in the presence of anti-CD20 Ab (23,24). Conversely, we showed that IFN-DC quickly formed conjugates with NK cells and that two independent mechanisms were synergistically operating in NK cell activation by IFN-DC: expression of MICA/B receptors on IFN-DC and their interaction with the cognate receptor NKG2D on NK cells, as well as trans-presentation of membrane-bound IL-15 by IFN-DC to NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14][15] In the prerituximab era, a mixed T-cell gene signature was associated with improved outcomes, whereas an expression signature enriched for monocyte genes was associated with poor prognosis. 10 Recent studies suggest, however, that the therapeutic setting may impact these associations, with macrophage infiltration correlating with worse outcomes after rituximab, cyclophosphamide, vincristine, and prednisone, but improved outcomes among patients treated with rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone.…”
Section: Introductionmentioning
confidence: 99%